Mir-30d Regulates Cardiac Remodeling by Intracellular and Paracrine Signaling. Issue 1 (8th January 2021) - Li, Jin; Salvador, Ane M.; Li, Guoping; Valkov, Nedyalka; Ziegler, Olivia; Yeri, Ashish; Yang Xiao, Chun; Meechoovet, Bessie; Alsop, Eric; Rodosthenous, Rodosthenis S.; Kundu, Piyusha; Huan, Tianxiao; et al.
Abstract : Rationale: Previous translational studies implicate plasma extracellular microRNA-30d (miR-30d) as a biomarker in left ventricular remodeling and clinical outcome in heart failure (HF) patients, although precise mechanisms remain obscure. Objective: To investigate the mechanism of miR-30d–mediated cardioprotection in HF. Methods and Results: In rat and mouse models of ischemic HF, we show that miR-30d gain of function (genetic, lentivirus, or agomiR-mediated) improves cardiac function, decreases myocardial fibrosis, and attenuates cardiomyocyte (CM) apoptosis. Genetic or locked nucleic acid–based knock-down of miR-30d expression potentiates pathological left ventricular remodeling, with increased dysfunction, fibrosis, and cardiomyocyte death. RNA sequencing of in vitro miR-30d gain and loss of function, together with bioinformatic prediction and experimental validation in cardiac myocytes and fibroblasts, were used to identify and validate direct targets of miR-30d. miR-30d expression is selectively enriched in cardiomyocytes, induced by hypoxic stress and is acutely protective, targeting MAP4K4 (mitogen-associate protein kinase 4) to ameliorate apoptosis. Moreover, miR-30d is secreted primarily in extracellular vesicles by cardiomyocytes and inhibits fibroblast proliferation and activation by directly targeting integrin α5 in the acute phase via paracrine signaling to cardiac fibroblasts. In the chronic phase of ischemic remodeling, lower expression of miR-30d in the heart and plasma extracellular vesicles is associated with adverse remodeling in rodent models and human subjects and is linked to whole-blood expression of genes implicated in fibrosis and inflammation, consistent with observations in model systems. Conclusions: These findings provide the mechanistic underpinning for the cardioprotective association of miR-30d in human HF. More broadly, our findings support an emerging paradigm involving intercellular communication of extracellular vesicle–contained miRNAs (microRNAs) to transregulate distinct signaling pathways across cell types. Functionally validated RNA biomarkers and their signaling networks may warrant further investigation as novel therapeutic targets in HF. Abstract : Supplemental Digital Content is available in the text.